Corporate social responsibility disclosure (CSRD) quality in Indonesian public listed companies - Ikbar, Pratama; Che Adam, Noriah; Kamardin, Hasnah (Index Copernicus Ltd, 2019)
Corporate social responsibility disclosure (CSRD) research trends shows a growing absence of information thoroughness and a decline in its trustworthiness, creating apprehension about the whole practice in reporting. The objective of this study is to determine the quality of the current CSRD on environmental and social information disclosure of Indonesian public listed companies (PLC) in the 2017 annual report, according to the latest GRI standards which is effective in 2018 as a guideline comprised of 25 items which is comply in Indonesia. The data collected were based on the environment and social items disclosed in annual reports published by all sectors of the company excluding banking and financial firms and companies with missing data of the year 2017. Descriptive analysis and multiple regression model are applied in this study and estimated using SPSS version 22. We found that the score of CSRD quality among the Indonesian PLC is mediocre. The average score of CSRD quality indicates that Indonesian PLC struggle to satisfy stakeholders’ expectation.